The Globalization of Tax Policy: What German Politicians Believe - Friedrich Heinemann; Eckhard Janeba (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
The process of globalization has an important impact on national tax policies. Most of the literature on taxation of capital in open economies does not focus directly on the political decision making process and assumes that the desired tax policy is responding to objective underlying tradeoffs. Based on an original survey of members of German national parliament (Bundestag) in 2006/7 we document a strong ideological bias among policy makers with respect to the perceived mobility of international tax bases (mobility of real capital and shifting of paper profits). Ideology via party affiliation influences also directly and indirectly the perceived national autonomy in tax setting and preferences for a EU minimum tax for companies. There seems little consensus as to what the efficiency cost of capital taxation in open economies are, even though our survey falls in period of extensive debate about and actual adoption of a company tax reform bill in Germany.
Keywords: H25; D83; D78; 330; Globalization; business taxation; tax competition; beliefs; member of parliament; Steuerwettbewerb; Unternehmensbesteuerung; Politiker; Meinung; Ideologie; Deutschland